2002
DOI: 10.3171/spi.2002.97.1.0110
|View full text |Cite
|
Sign up to set email alerts
|

Pilocytic astrocytoma of a spinal nerve root

Abstract: ✓ A case of pilocytic astrocytoma involving a spinal nerve root is reported. A 39-year-old woman presented with a 1-year history of progressive pain and numbness, predominantly in the S-1 dermatome. Magnetic resonance (MR) imaging revealed an intradural lesion at the tip of the conus medullaris. The intradural tumor was excised as was the sacrificed nerve root. Histological examination showed a pilocytic astrocytoma in which there were unusual features of calcification and oss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Gilles et al 14 noted parenchymal calcification more among older children, while Philipson et al 30 observed calcification and ossification in a case of PA involving spinal nerve root in a 39-year-old woman. Dierssen et al 11 also described extensive calcification in a case of pontine PA. Maruyama et al 28 and Lee et al 24 reviewed the CT and MR characteristics of juvenile pilocytic astrocytomas and noted tumor calcification in occasional cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gilles et al 14 noted parenchymal calcification more among older children, while Philipson et al 30 observed calcification and ossification in a case of PA involving spinal nerve root in a 39-year-old woman. Dierssen et al 11 also described extensive calcification in a case of pontine PA. Maruyama et al 28 and Lee et al 24 reviewed the CT and MR characteristics of juvenile pilocytic astrocytomas and noted tumor calcification in occasional cases.…”
Section: Discussionmentioning
confidence: 99%
“…Other features that are variably present in PA include sclerotic vessels, vascular proliferation, calcification 7,11,14,24,27,28,30 and chronic inflammation, 7,14,27 while nuclear pleomorphism, mitosis and necrosis are rare. Owing to the differences in prognosis and therapeutic options, it is vital to distinguish PA from diffuse astrocytoma, and in the presence of mitosis / necrosis from other high-grade neoplasm.…”
mentioning
confidence: 99%
“…1 Two cases of astrocytoma located at a nerve root histologically corresponded to pilocytic astrocytoma. 2,3 We report on a unique case of a solitary, primarily intradural, extramedullary anaplastic astrocytoma arising from the first sacral nerve root. …”
Section: Discussionmentioning
confidence: 99%
“…Primary spinal PA requires surgical resection similar to other intramedullary spinal tumors (7), but there is no clear evidence that adjuvant radio-and/or chemo-therapy treatments after surgery might be necessary. To date, only a few spinal cord PA, either case reports or sporadic ones, have been described in their genetic and molecular characteristic signatures (8)(9)(10)(11)(12)(13). The most recurrent genetic alterations in WHO Grade I spinal cord astrocytomas are BRAF-KIAA1549 translocation, BRAF copy number gain and the BRAFV600E single nucleotide variation.…”
mentioning
confidence: 99%